2022
DOI: 10.1371/journal.pone.0274116
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of RIP1-RIP3-mediated necroptosis attenuates renal fibrosis via Wnt3α/β-catenin/GSK-3β signaling in unilateral ureteral obstruction

Abstract: Renal fibrosis represents the final common outcome of chronic kidney disease of virtually any etiology. However, the mechanism underlying the evolution of renal fibrosis remains to be addressed. This study sought to clarify whether RIP1-RIP3-mediated necroptosis is involved in renal fibrosis via Wnt3α/β-catenin/GSK-3β signaling in vitro and in a rat model of unilateral ureteral obstruction (UUO). Rats with UUO were administered RIP inhibitors (necrostatin-1 or GSK872) or β-catenin/TCF inhibitor ICG-001 daily f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…A previous study showed that necroptosis plays a more significant role in mediating tubular cell injury than apoptosis in the subtotal nephrectomy model of CKD [ 81 ]. Moreover, recent studies have shown that inhibition of necroptosis attenuated UUO-induced renal interstitial fibrosis and inflammation [ 82 , 83 ]. In this study, CS treatment remarkably inhibited UUO-induced apoptosis and necroptosis, as evidenced by a decrease in the number of TUNEL-positive cells and the expression of key factors related to apoptosis (cleaved caspase-3, cleaved PARP-1, p53 and Bax) and necroptosis (RIPK1, RIPK3 and MLKL).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that necroptosis plays a more significant role in mediating tubular cell injury than apoptosis in the subtotal nephrectomy model of CKD [ 81 ]. Moreover, recent studies have shown that inhibition of necroptosis attenuated UUO-induced renal interstitial fibrosis and inflammation [ 82 , 83 ]. In this study, CS treatment remarkably inhibited UUO-induced apoptosis and necroptosis, as evidenced by a decrease in the number of TUNEL-positive cells and the expression of key factors related to apoptosis (cleaved caspase-3, cleaved PARP-1, p53 and Bax) and necroptosis (RIPK1, RIPK3 and MLKL).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that this necrotic induction of NCB0846 in mammary epithelial cells may have occurred through the WntβcateninNFκB axis. Indeed, many studies have proven that Wnt/βcatenin signaling mediates necroptosis [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Immunoblotting was performed as described previously [ 4 , 19 ]. The primary antibodies were used as follows: transforming growth factor-beta1 (TGF-β1, #ab179695, Abcam), connective-tissue growth factor (CTGF, #ab6992, Abcam), pro-interleukin-1beta (pro-IL-1β, #ab9722, Abcam), pro-IL-18 (#ab191860, Abcam), NOD-like receptor pyrin domain-containing protein 3 (NLRP3, #ab214185, Abcam), tumor necrosis factor-alpha (TNF-α, #ab205587), inducible nitric oxide synthase (iNOS, #ab178945), superoxide dismutase-2 (SOD2/MnSOD, #ab13534, Abcam), thioredoxin (TRX, #ab109385), thioredoxin-interacting protein (TXNIP, #ab188865), Parkin (#2132, Cell Signaling Technology), succinate dehydrogenase complex subunit A (SDHA, #ab66484, Abcam), C/EBP homologous protein (CHOP, L63F7, #2895, Cell Signaling), inositol-requiring protein-1α (IRE-1α, phospho S724, #ab37073, Abcam), B-cell lymphoma-2 (Bcl-2, #ab196495, Abcam), Bcl2-associated X (Bax, #ab32503, Abcam), p-JNK (#ab76572), p-MEK4 (#4514, Cell Signaling), p-ASK1 (#ab278547), p-P38 (#ab4822), p-MEK3 (#ab79586), beta actin (β-actin, #ab8226, Abcam).…”
Section: Methodsmentioning
confidence: 99%